Antioxidative properties of selected Malaysian herbal plants - Yusuf, Sumazian (2014)
Antioxidant activities of nine herbal plants which are commonly used in Malaysia as folk medicines, namely Barringtonia racemosa (putat), Curcuma domestica (kunyit), Kaempferia galanga (cekur), Hydrocotyle bonariensis (pegaga embun), Centella asiatica (pegaga), Piper betel (sireh), Polygonum minus (kesum), Piper sarmentosum (kadok) and Cosmos caudatus (ulam raja) were examined. All of the herbs selected for all readily available for everyday use with a variety of uses well known since time immemorial. The study was conducted to see the appropriate dose to be used for commercial purposes. The compounds in leaf and rhizome were extracted using hot water (100 0C), fresh water and ethanol (80%), separately. Total antioxidant content were measured using ferric reducing power (FRAP), 1,1 diphenyl -2- picrylhydrazyl free radical scavenging assay (DPPH) and X-carotene bleaching assay. Subsequently, the relevant antioxidant compounds; total carotenoids, total ascorbic, total flavonoids and total phenolic. Enzymatic antioxidants include superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), catalase (CAT) and peroxidase (POX) activities were determined. Anti-aging enzymes activities; anti-tyrosinase, anti-elastase and anti-hyaluronidase were also determined using spectrophotometry method. For FRAP assay, hot water extract of C. domestica (623.87 ± 0.01 mmol Fe2+/g DW) showed good activity and fresh water extractMof K. galanga exhibited a very strong antioxidant properties in DPPH assay with (83.27 ±0.01%). H. bonariensis leaf extract has been recognized to contain high antioxidant activity with (19.04 ± 0.01 %) using X-carotene bleaching assay. The rhizome extract of C.domestica showed the highest total carotenoid content of (0.04 ± 0.01 mg/mg FW) and leaf extract of P. sarmentosum indicated (1.72 ± 0.01 mg/g FW) for the highest total of ascorbic acid content. Level of total flavonoids in the herbal plants varied between (0.42 ± 0.00 and 6.28 ± 0.01 mg/g DW) and those of total phenolics between (2.78 ± 0.01 and 12.35 ± 0.01 mg/g DW). For enzymatic antioxidant activities, the results showed that C.domestica (0.42 ± 0.01 μmol/min/g FW), P. sarmentosum (0.14 ± 0.01 μmol/min/g FW),C. asiatica (0.76 ± 0.01 μmol/min/g FW), H. bonariensis (0.92 ± 0.01 μmol/min/g FW) and P. minus (0.38 ± 0.01 μmol/min/g FW) were higher in SOD, APX, GR, CAT and POX activity, respectively. The highest percentage of anti-tyrosinase activity is in fresh water extract of C. domestica rhizome (97.86 ± 0.02 %) using L-tyrosine as substrate. C.asiatica leaf exhibited a very good level of elastase and hyaluronidase inhibition with (84.53 ± 0.02%) and (81.01 ± 0.01%), respectively. The findings showed the potential of nine medicinal plants as powerful antioxidant that can be used in producing herbal based product in cosmetically and pharmaceutical.